SWOT-AHP Integrated Strategic Analysis of Culinary MSMEs: Optimizing Product Diversification to Increase Sales - Chaerunnisa Najib; Tuti Supatminingsih; Muhammad Hasan; Muhammad Asiz; Najamuddin; Najib, Marhawati (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study aims to analyze internal and external environmental factors affecting MSMEs in the culinary sector and to formulate appropriate strategic alternatives for business development using SWOT-AHP integration. A mixed-methods approach, combining qualitative and quantitative techniques, was employed. Data were collected through observations, interviews, and questionnaires, utilizing both primary and secondary data sources. Analysis tools included Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE) Matrix, SWOT Matrix, and Analytical Hierarchy Process (AHP) using Expert Choice software. The results indicated an IFE total score of 2.74 and an EFE total score of 2.39, placing the MSME within the growth quadrant (Quadrant I), which signifies a strong position for leveraging internal strengths and external opportunities. Based on SWOT analysis, the Strength-Opportunity (SO) strategies recommended include maintaining and enhancing service quality to ensure customer loyalty, leveraging product diversification to increase sales, and utilizing brand ambassadors for effective promotion. Weakness-Opportunity (WO) strategies involve pricing adjustments based on market conditions and quality enhancement to retain customers. Strength-Threat (ST) strategies recommend maintaining product quality despite rising raw material costs to sustain customer retention. Lastly, Weakness-Threat (WT) strategies suggest expanding market reach and intensifying promotional activities to remain competitive. The AHP analysis identified the most prioritized strategic alternative: leveraging product diversification to enhance sales volume. This study contributes practical insights for culinary MSMEs seeking sustainable growth and improved market competitiveness.